2016
DOI: 10.4028/www.scientific.net/amm.861.167
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study on Thermal Performance of a Ventilated PV Façade Coupled with PCM

Abstract: This paper presents a dynamic thermal model based on DesignBuilder simulation software platform, for a simple office building model with an integrated ventilated PV façade/solar air collector system in climatic conditions of Bratislava, Slovakia. Thermodynamic simulation has been applied in order to express thermal performance of a ventilated PV façade coupled with phase change material through the whole reference year. Attention is focused on simplified approaches which capture the important elements of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Through experiments and transient energy balance approach, Hachem et al [15] and Kibria et al [16] studied the effect of PCM on the performance of PV board and concluded that PCM could decrease the temperature of PV board and increase the electrical efficiency. Curpek and Hraska [17] compared and studied the PV board with and without PCM as well as the flow passage with and without ventilation, the results showed that natural ventilation of PV façade with added PCM could reduce the temperature of PV board better. Aelenei et al [18,19] developed a simplified thermal network model for BIPV-PCM and studied the thermal behavior of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Through experiments and transient energy balance approach, Hachem et al [15] and Kibria et al [16] studied the effect of PCM on the performance of PV board and concluded that PCM could decrease the temperature of PV board and increase the electrical efficiency. Curpek and Hraska [17] compared and studied the PV board with and without PCM as well as the flow passage with and without ventilation, the results showed that natural ventilation of PV façade with added PCM could reduce the temperature of PV board better. Aelenei et al [18,19] developed a simplified thermal network model for BIPV-PCM and studied the thermal behavior of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the customization level, four were purely elemental [51,52,80,82], eight were compositional at the module-level [64,81,83,88,89,91,92,95], and five were compositional at the façade-level [17,53,81,84,94]; eight studies combined all of the levels [55,82,[85][86][87]90,93,96]. Comparing elemental versus compositional level, studies can be more easily carried out using conventional PV modules without the requirement of a custom-designed module.…”
Section: Innovation and Custom Categorymentioning
confidence: 99%
“…Statistically, nine of the cases focused on design of a custom BIPV product [51,52,55,[80][81][82][83]89,95], only four focused on a customization in the integration process [63,81,84,94], while 12 combined both product and integration concerns in their research [17,53,63,64,[85][86][87][88][90][91][92][93]. This suggests that most custom BIPV façade products are designed with attention on the potential for proper architectural integration.…”
Section: Innovation and Custom Categorymentioning
confidence: 99%
See 2 more Smart Citations